Two new species of fungus gnats (Diptera: Mycetophilidae) from Kunashir Island, Kuril Islands - Zaitzev, Alexander (Zootaxa, 2017)
Two new species of Mycetophilidae (Diptera), Clastobasis subalternans sp. n. and Phthinia kurilensis sp. n. are described from Kunashir I. (South Kuril Is.). Their relationships with other species of Clastobasis Skuse and Phthinia Winnertz are briefly discussed.